PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA TEMA LINGKUNGAN SAHABAT KITA KELAS V SDN 173417 POLLUNG DAN SDN 173420 POLLUNG - Khaty Dian Situmorang; Reflina Sinaga; Sumarlin Mangandar Marianus; Darinda Sofia Tanjung (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the effect of using mind mapping as a learning model on students’ learning outcomes on environmental material at grade V of SDN Pollung District in the academic year 2020/2021. The research in this article used descriptive analysis techniques. The population involved grade V students at SDN Pollung, which consisted of two schools, SD Negeri 173417 and SD Negeri 173420. The research outcomes indicated that students’ learning outcomes using the mind mapping model were very good with an average category score of 84.72. The research outcomes also indicated that the results of the correlation test came from a correlation number of 0.620. It means that if rcount (0.620) > rtable (0.217), hence Ha is accepted. Thus, there is a big influence between the mind mapping learning model and students’ learning outcomes with the theme of our friend environment at grade V of SDN Pollung. It also could be found from the results of the t-test where tcount 6,984 > ttable 1,664, hence Ha is accepted. It shows that there is a significant positive effect of applying Mind Mapping toward students’ learning outcomes with the theme of our friend environment at grade V of SDN Pollung in the academic year 2021/2022.